2017
DOI: 10.1038/s41598-017-17496-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of REV-ERB stimulates differentiation, inhibits turnover and reduces fibrosis in dystrophic muscle

Abstract: Duchenne muscular dystrophy (DMD) is a debilitating X-linked disorder that is fatal. DMD patients lack the expression of the structural protein dystrophin caused by mutations within the DMD gene. The absence of functional dystrophin protein results in excessive damage from normal muscle use due to the compromised structural integrity of the dystrophin associated glycoprotein complex. As a result, DMD patients exhibit ongoing cycles of muscle destruction and regeneration that promote inflammation, fibrosis, mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 68 publications
3
27
4
Order By: Relevance
“…The data indicates that partial loss of Nr1d1 gene does not produce deleterious effects and effectively augments metabolic substrate preference. This aligns well with our previous studies in which we showed that REV-ERB inhibition is an effective approach for pharmacologically stimulating muscle repair [16,17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The data indicates that partial loss of Nr1d1 gene does not produce deleterious effects and effectively augments metabolic substrate preference. This aligns well with our previous studies in which we showed that REV-ERB inhibition is an effective approach for pharmacologically stimulating muscle repair [16,17].…”
Section: Discussionsupporting
confidence: 92%
“…Previously, we have highlighted that REV-ERB directs myogenesis through tethered interaction with the transcription complex Nuclear Factor-Y [16]. Moreover, inhibiting REV-ERB with a synthetic antagonist enhanced muscle repair in an acute injury model and slowed disease progression in a model of Duchenne's muscular dystrophy [16,17]. Loss of Rev-Erb in contrast to Rev-Erb was also shown to stimulate skeletal muscle metabolism and fatty acid oxidation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Our data thus support the idea that specifically inhibiting muscle REV-ERBα/β [ 124 ] in certain situations may provide a relatively safe means to temporarily modulate metabolic efficiency and EE in skeletal muscle, a major oxidative tissue and relevant pharmacological target in humans [ 125 , 126 ]. Indeed, pioneering groups have already begun to wade into these therapeutic waters and, importantly, have already shown in mice that selective REV-ERB antagonism accelerates muscle regeneration in response to acute muscle injury [ 99 ] and promotes muscle differentiation and maintenance of muscle mass in a model of Duchenne muscular dystrophy (DMD) [ 127 ]. Intriguingly, Welch and colleagues showed REV-ERB antagonism enhances Wnt and Notch signaling, leading to satellite cell self-renewal.…”
Section: Discussionmentioning
confidence: 99%
“…To further understand the Bmal1‐related mechanism on a cellular level, we used synchronized rat cardiomyocytes (H9c2), a cell line derived from rat heart. Cardiomyocytes have been shown to exhibit robust circadian rhythms, and recent studies showed that antagonism of the Bmal1 repressor protein, Rev‐erbα, offered cardioprotection to cardiac surgery patients from perioperative myocardial ischaemia‐reperfusion injury and reduced fibrosis in dystrophic muscle . Hence, we reasoned that decrease in Bmal1 via increased Rev‐erbα will be deleterious in cardiomyocytes.…”
Section: Resultsmentioning
confidence: 97%
“…Cardiomyocytes have been shown to exhibit robust circadian rhythms, 15 and recent studies showed that antagonism of the Bmal1 repressor protein, Rev-erbα, offered cardioprotection to cardiac surgery patients from perioperative myocardial ischaemia-reperfusion injury and reduced fibrosis in dystrophic muscle. [43][44][45] Hence, we reasoned that decrease in Bmal1 via increased Rev-erbα will be deleterious in cardiomyocytes. To test this, we treated H9c2 cells with 25 µM of the Rev-erbα agonist, SR9011, to inhibit Bmal1 compared to DMSO controls, with maximum effect seen at 48 hours ( Figure S4D).…”
Section: Bmal1 Depletion Sensitizes Cardiomyocytes To Ir-induced Damentioning
confidence: 99%